2016
DOI: 10.21082/ijas.v7n1.2006.15-19
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Postharvest Machineries and Packaging in Minimizing Aflatoxin Contamination in Peanut

Abstract: As a tropical country with relatively high humidity and temperature, Indonesia is struggling with aflatoxin which frequently contaminates peanut. Aflatoxin is a carcinogenic toxic substance that could cause liver cancer. Due to the increasing concern on food safety, the Indonesian Drugs and Foods Agency specifies the maximum aflatoxin allowed in peanut as much as 20 ppb. However, researches showed that aflatoxin contamination in peanut in Indonesia is much higher than the threshold. The study was carried out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Hepsag et al detected total levels of aflatoxins in pistachio samples, ranging from 0.26 µg/kg to 385 µg/kg and from 0.16 to 60.9 µg/kg in groundnuts [ 48 ]. Fu et al, 2018 found in their study that PET is more suitable to store peanuts, pistachios, and other oleaginous products due to its good properties for maintaining the safety of the products [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hepsag et al detected total levels of aflatoxins in pistachio samples, ranging from 0.26 µg/kg to 385 µg/kg and from 0.16 to 60.9 µg/kg in groundnuts [ 48 ]. Fu et al, 2018 found in their study that PET is more suitable to store peanuts, pistachios, and other oleaginous products due to its good properties for maintaining the safety of the products [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mold-affected kernels must be removed for consumption. Paramawati et al (2006) showed postharvest machines such as threshers, dryers, and shellers improve yield and reduce processing and drying time. As a result, they are often linked to lower aflatoxin contamination in groundnuts.…”
Section: Imentioning
confidence: 99%
“…The use of hermetic triple-layer bags (PICS, Purdue Improved Crop Storage) for grain and kennel storage has proved effective against aflatoxin contamination over traditional storage devices (Murdock et al, 2003;Hell et al, 2010). Studies on hermetic packaging have showed that hermetic packages and containers are capable of protecting groundnuts from moulds and aflatoxin contamination (Paramawati et al, 2006). Apart from the storage containers, the condition of the kernels and the prevailing conditions in the storage structure are important factors that can influence aflatoxin contamination.…”
Section: Inmentioning
confidence: 99%